Argumentacja i emocje w sporach polonistów O peryferyjnej ramie w krytyce naukowej na przykładzie polemik zamieszczonych w „Pamiętniku Literackim” - Budzyńska-Daca, Agnieszka (Śląskie Studia Polonistyczne, 2015)
The aim of the paper was the analysis of the scientific disputes published in ”Pamiętnik Literacki” in the “Dyskusje – Korespondencja” section, and previously ”Polemika”, ”Dyskusje i Polemiki”, and ”Korespondencja”, from 1902 till 2008. The author of the paper has formulated the idea of the peripheral frame which describes the type of argumentation of a peripheral character which, nonetheless, introduces essential arguments into a discussion. While analysing the disputes published in ”Pamiętnik Literacki” the author of the paper has observed some repeated elements of the refutation frame which have a peripheral character, surrounding the subject and modulating the statement’s persuasion-ability. The frame elements can also be found in the sphere of inventive, thematic and disposable topos related to the composition limits. Among their most important mutual points (loci communes) there are: concern of the reader argumentation like ad auditores), meta-polemic remarks, adminicula, or, in other words, reference to a dispute circumstances, causa scribendi, or refutation reasons, an opponent’s evaluation, or a group of arguments ad hominem.